Doctor - Cream Production ([Taiwan : Cream Production, 2006)
On US independent day, 1996, Taiwanese-American 13-years-old genius Felix posted a puzzling notice on his bedroom door. Three hours later, he had ended his own life. Devastated, his father, Dr. Wen, Left Iowa City, his home of twenty years, and moved to Miami. Though the sunny, warm clime and passage of time have distanced him from the traumatic experience, his grief and perplexity linger. Six years after Felix's death, a boy from Peru, Sebastian, comes to receive treatment for cancer from Dr. Wen. Through the stories of two adolescents and Dr. Wen's loving concern for them, the documentary'Doctor' portrays with touching compassion the transeince, struggles, mysteriousness, and preciousness of life
DVD Format
Subtitles in Tradisional Chinese, English, French and Spanish
Keywords: Fathers and sons; Cancer -- Treatment